1988
DOI: 10.1007/bf00175403
|View full text |Cite
|
Sign up to set email alerts
|

A phase II evaluation of cisplatin in unresectable diffuse malignant mesothelioma: A Southwest Oncology Group Study

Abstract: Cisplatin was given intravenously to 35 evaluable patients with unresectable malignant mesothelioma on Southwest Oncology Group (SWOG) Study 8418. Five patients (14.3%) achieved partial response with median response duration of six months (range 2-12 months); eleven patients (31.4%) had stable disease of median duration of 5.5. months (range 2-21 months). Median survival for all patients was 7.5 months, 9 months for responders. Toxicity was as expected except that 12 patients (34.2%) discontinued cisplatin bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(21 citation statements)
references
References 4 publications
0
20
0
1
Order By: Relevance
“…Neither cisplatin with a response rate of 13 -14% (Mintzer et al, 1985;Zidar et al, 1988), nor gemcitabine (response rate 0 -31%) (Bischoff et al, 1998;van Meerbeeck et al, 1999;Kindler et al, 2001) have shown great promise as single agents in the treatment of this disease. The additive or synergistic interaction of the two drugs documented in vitro (Peters et al, 1995) and in animal models (Peters et al, 1996) may underlie the useful clinical effects demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Neither cisplatin with a response rate of 13 -14% (Mintzer et al, 1985;Zidar et al, 1988), nor gemcitabine (response rate 0 -31%) (Bischoff et al, 1998;van Meerbeeck et al, 1999;Kindler et al, 2001) have shown great promise as single agents in the treatment of this disease. The additive or synergistic interaction of the two drugs documented in vitro (Peters et al, 1995) and in animal models (Peters et al, 1996) may underlie the useful clinical effects demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Single-agent cisplatin resulted in a response rate of merely 14.3% and a median survival of 7.5 months (Zidar et al, 1988). Studies using the newer compound carboplatin resulted in similar response rates ranging between 6 and 16% (Mbidde et al, 1986;Raghavan et al, 1990;Vogelzang et al, 1990).…”
Section: Single-agent Chemotherapymentioning
confidence: 98%
“…Similarly, cisplatin alone achieves a response rate of only 14% of cases at standard dosage and up to 33% at high dosage [83][84][85][86][87]. High doses of methotrexate alone obtain responses in 37% of cases [88].…”
Section: Chemotherapymentioning
confidence: 99%